Penanganan Guest Request oleh Guest Service Center di Department Front Office Hotel Sheraton Mustika Yogyakarta Resort & Spa - Akh. Fajar Rahman; Sri Sukarni Gestuti (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
Handling Guest Requests by the Guest Service Center in the Front Office Department at Sheraton Mustika Yogyakarta Resort & Spa.In the era of globalization and rapid growth in the tourism industry, hotel service has become a crucial aspect in ensuring customer satisfaction. The COVID-19 pandemic has changed the dynamics of the hospitality industry, and as recovery progresses, it is important for hotels to enhance the quality of their services to attract customers back. Sheraton Mustika Yogyakarta Resort & Spa, with its unique architecture and luxurious facilities, has seen an increase in occupancy post-pandemic, especially during high seasons like religious celebrations and major holidays. The task of ensuring customer satisfaction is handled by the Guest Service Center, and it is not an easy task. This department serves as the hub for all guest information and requests, acting as the front line in direct contact with hotel guests. Every agent in the Guest Service Center must possess skills such as proper speaking etiquette, telephone etiquette, quick response, and diplomatic actions to achieve a good image, ensuring that guests are satisfied with the service provided. The purpose of this research is to analyze the request handling process, identify the challenges, and find the solutions implemented by the Guest Service Center at Sheraton Mustika Yogyakarta Resort & Spa. The results of this research are expected to be used to improve service quality and has been assisted with a good customer complaint handling system.